The Effect of Menopause Psychoeducation on Anxiety in Facing Menopause Among Premenopausal Women at Jaboi Health Center, Sabang - Nisa Firdausi; Syarifah Masthura; Dewi Sartika (International Journal of Health and Social Behavior, 2025)
Menopause is a natural biological transition that often presents with health issues such as anxiety, sleep disturbances, and mood changes, which may negatively affect women’s quality of life. With the growing number of women entering menopause worldwide, including in Indonesia, effective interventions are needed to help them adapt positively. This study aimed to evaluate the effect of psychoeducation on anxiety levels among premenopausal women in the working area of the Jaboi Community Health Center, Sabang City. A quantitative quasi-experimental pre–post design without a control group was employed. The study involved 60 premenopausal women selected through purposive random sampling from a population of 146. The intervention, conducted from May 16 to June 10, 2025, consisted of structured psychoeducational sessions designed to increase knowledge and coping abilities related to menopause. Data were analyzed using the Wilcoxon signed-rank test. Results showed that the mean anxiety score decreased significantly from 20.13 (moderate category) before the intervention to 18.17 after the intervention (p < 0.001). These findings indicate that psychoeducation effectively reduces anxiety and enhances preparedness among premenopausal women. It is therefore recommended that routine psychoeducational counseling be integrated into primary healthcare services as a promotive effort to support women in facing menopause in a healthier and more confident manner.